2016
DOI: 10.1111/bjh.14021
|View full text |Cite
|
Sign up to set email alerts
|

Results of a multicentre UK‐wide retrospective study evaluating the efficacy of pixantrone in relapsed, refractory diffuse large B cell lymphoma

Abstract: Relapsed or refractory (R/R) diffuse large B-cell lymphoma (DLBCL) in those unfit or ineligible for autologous stem cell transplantation is associated with a poor outcome and new treatment approaches are needed. Pixantrone is a novel aza-anthracenedione which is structurally similar to anthracyclines and is licenced in R/R DLBCL and National Institute for Health and Care Excellence (NICE)-approved following the PIX301 trial. No data exist post-NICE approval. We performed a UK-wide retrospective multi-centre st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
32
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 22 publications
5
32
2
Order By: Relevance
“…33 Another study using 131 I-tositumomab-BEAM in comparison with rituximab-BEAM did not reveal any differences between the 2 arms. 34 In a phase 2 study with 131 I-tositumomab given as consolidation after R-CHOP, the CR rate and PFS were not better than with R-CHOP alone in this patient subset. 35 In another phase 2 study with 90 Y-ibritumomab tiuxetan consolidation after R-CHOP, a longer PFS was observed than is usually described (5-year PFS, 78%).…”
Section: Patients Not Eligible For Transplantmentioning
confidence: 85%
“…33 Another study using 131 I-tositumomab-BEAM in comparison with rituximab-BEAM did not reveal any differences between the 2 arms. 34 In a phase 2 study with 131 I-tositumomab given as consolidation after R-CHOP, the CR rate and PFS were not better than with R-CHOP alone in this patient subset. 35 In another phase 2 study with 90 Y-ibritumomab tiuxetan consolidation after R-CHOP, a longer PFS was observed than is usually described (5-year PFS, 78%).…”
Section: Patients Not Eligible For Transplantmentioning
confidence: 85%
“…10 The first real-world data on pixantrone were published in 2016; a UK-based retrospective study has suggested that patients who relapse >12 months after first-line treatment, those with fewer prior lines of therapy, and relapsed (non-refractory) DLBCL gain greater benefit from pixantrone compared with patients who relapse earlier, have had more lines of prior therapy, or have refractory DLBCL. 11 Despite this evidence, data on the use of pixantrone in everyday clinical practice remain scarce.…”
mentioning
confidence: 99%
“…The PIX301 trial found a modest progression‐free survival (PFS) advantage with pixantrone monotherapy compared to investigators’ choice of alternative monotherapy, but only recruited 140 patients from 66 centres, of a population which does not represent most patients with relapsed lymphoma. A UK‐wide retrospective study of pixantrone, with a ‘real‐world’ population of older and more frail patients, found worse responses and shorter survival (Eyre et al , 2016b). Furthermore, a press release from the PIX306 trial in July 2018 reported no benefit to R‐pixantrone over R‐gemcitabine (A. Craig, unpublished observations).…”
Section: Palliative Oral Regimens For Relapsed Lymphomamentioning
confidence: 99%